Comparative Assessment of Performance-Based Design Methodologies Applied to a R.C. Shear-Wall Building - Juan C. Vielma-Quintero; Jorge Carvallo; Juan C. Vielma (Buildings, 2023)
Performance-based design has been increasingly used in practice due to computational improvements, the sophistication and dissemination of nonlinear analysis methods, and the development of commercial programs that facilitate its use. We can evaluate the nonlinear effects of seismic events of great magnitude on the structural behavior of a building, verify preliminary designs based on force-based methods, validate standard design regulations, determine deformations, and calculate accelerations that can be translated into parameters of structural damage and economic losses, among other functions. Guiding documents have presented methodologies to establish requirements, evaluation criteria, analysis methods, etc., each with different objectives, revealing the lack of a consensus method. In this paper, the state of the art of performance-based design is studied, and some of the most relevant methods, such as ASCE 41-17, ASCE 7-16, and the alternative procedure of ACHISINA, are applied to a structure with shear walls designed according to current Chilean regulations. Additionally, modal-response spectrum analysis is used. The modeling of the earthquake-resistant structure of the building, the preparation of seismic records, and the consideration of aspects that limit the rigorous application of the method are addressed in a nonelastic analysis framework. Results obtained in the respective analyses that are used to evaluate the structural performance are compared with the corresponding performance criteria for each standard, considering the characteristics of each methodology. Moreover, the main complications that can occur during the application of the methods are discussed.